E-Sexual Health: A Position Statement of the European Society for Sexual Medicine. Issue 7 (24th April 2020) - Kirana, Paraskevi-Sofia; Gudeloglu, Ahmet; Sansone, Andrea; Fode, Mikkel; Reisman, Yacov; Corona, Giovanni; Burri, Andrea
Abstract: Background: Opportunities and pitfalls of e-health have been described and assessed in various health domains, but in the field of sexual health, the respective literature is limited. Aim: The aim of this document is to present the European Society of Sexual Medicine's (ESSM) current position statement on e-sexual health. Methods: This statement article is an expert opinion–based proposal that was developed under the auspices of the ESSM with input from the e-sexual health subcommittee of the ESSM Scientific Committee. Outcomes: ESSM statements were provided on four domains: health information for patients, e-learning for professionals, health interventions, and health research. Results: e-Sexual health is the use of information and communication technologies for sexual health including sexual health care, surveillance, education, knowledge, and research. Quality indicators have to be applied on Web pages that provide sexual health information, e-learning can increase educational opportunities for professionals, online treatment interventions can be effective but needs to be available to the public, and online health research can provide access to difficult to reach populations. Clinical Implications: The ESSM acknowledges the necessity for the use of information and communication technologies to meet the sexual health needs of citizens and patients and also the professional needs of sexual healthcare providers, in an evidence-based manner. Strengths & Limitations: ESSM statements on this topic were provided based on expert opinion and summarize the ESSM position in this field. Conclusion: The ESSM believes that e-sexual health can provide opportunities for the improvement of the sexual health of the population.